Metabolic resistance to deltamethrin is mediated by P450 and esterases in common bed bugs Cimex lectularius L. (Heteroptera: Cimicidae) - Cáceres, Mariano (2023)
The infestations of Cimex lectularius L. (Heteroptera: Cimicidae) registered in the last decades have been influenced by several human activities, including international tourism and commerce. Moreover, the development of insecticide resistance and careless pest control strategies contributed to the dispersal of bed bugs. Given the complexity of the topic, distinguishing physiological and molecular mechanisms involved in resistance can help design proper control tools and limit the resistance spread. Here we determined the susceptibility to deltamethrin and imidacloprid in bed bugs collected in Italy. Also, we assessed the role of esterases and P450 monooxygenases by direct enzymatic activity measurement and inhibition by synergism bioassays. Our results showed that the field-collected colony exhibited high resistance ratios to imidacloprid and deltamethrin (757 and >60,000 times, respectively) compared to the susceptible colony. Moreover, resistant bed bugs showed increased activity of esterases and P450 monooxygenases. The synergistic effect of piperonyl butoxide (PBO) suggests the significant contribution of both enzymatic groups as detoxification pathways implicated in pyrethroid-resistant bed bugs. Further investigations are needed to unravel the biochemical and molecular basis involved in the resistant phenotype for developing novel strategies for pest control.